Application of the Concept of Geometric Transformation to the Patterns and Proportions of Heritage Architecture of the Cirebon Kejaksan Station - Febri Yanti Nurcahya; Apriliyani Apriliyani; Yudha Bagus Aflihawa; Gina Rizkina; Arif Muchyidin (Journal of General Education and Humanities, 2026)
The architecture of cultural heritage buildings not only represents historical and aesthetic values but also exhibits a regularity in form that can be studied through mathematical approaches. This research aims to examine the application of the concept of geometric transformation in the architectural patterns and proportions of the cultural heritage of the Cirebon Kejaksan Office Station and to uncover its relationship with local cultural values through an ethnomathematical perspective. The research uses a qualitative descriptive approach, with visual observation and photographic documentation of the building's front appearance components, including doors, windows, vents, arches, and ornaments. The analysis is focused on identifying geometric transformations in the form of reflection, shift, and magnification based on patterns of repetition, symmetry, and scale variation of architectural components. The results of the research show that the front view of the Kejaksan's Station reflects strong bilateral symmetry, shifts through the consistent repetition of door and window modules, and enlarges through variations in component dimensions that maintain the harmony of shape. In addition, the geometric patterns observed are consistent with the principles of repetition and balance in Cirebon culture, thereby reflecting the acculturation of colonial architecture with local values. These findings confirm that the Kejaksan Station has the potential to serve as a source of contextual learning in transformation geometry.